Treatment of Atlas Fractures: Recommendations of the Spine Section of the German Society for Orthopaedics and Trauma (DGOU) - Kandziora, Frank (Global Spine J, 2018)
STUDY DESIGN: Narrative review and expert recommendation. OBJECTIVES: To establish treatment recommendations for atlas fractures based on the knowledge of the experts of the Spine Section of the German Society for Orthopaedics and Trauma. METHODS: Neither high-level evidence studies comparing conservative and operative management nor studies matching different operative treatment strategies exist. This recommendation summarizes the knowledge of the experts of the Spine Section of the German Society for Orthopaedics and Trauma with regard to the treatment of atlas fractures. RESULTS: Most atlas fractures are the result of compression forces. A valuable morphological classification system has been described by Gehweiler. For an adequate diagnosis, a computed tomography is mandatory. To distinguish between stable and unstable type 3 injuries, it is necessary to evaluate the integrity of the transverse atlantal ligament (TAL) with magnetic resonance imaging and to classify the TAL lesions. The majority of atlas fractures are stable and will be successfully managed conservatively. Unstable atlas fractures (type 3b and sagittal split type 4 fractures) should be treated by surgical stabilization. Unstable atlas fractures (type 3b) with a midsubstance ligamentous disruption or severely dislocated ligamentous bony avulsions of the TAL can successfully be treated by a C1/2 fusion. Unstable atlas fractures (type 3b) with a moderately dislocated ligamentous bony avulsion of the TAL and sagittal split type 4 fractures may be treated by atlas osteosynthesis only. CONCLUSIONS: Whereas the majority of atlas fractures can be managed conservatively, in specific fracture patterns surgical treatment strategies have become the standard of care.